Hydroxyalkylation of p-Cresol to 2,2 `-methylenebis(4-methylphenol) using Sn/Si-MCM-41 catalysts - Garade, Ajit C.; Niphadkar, Prashant S.; Joshi, Praphulla N.; Rode, Chandrashekhar V. (Chemistry Letters, 2010)
Sn/Si-MCM-41 has exhibited an excellent catalytic activity [70% product yield with 88% selectivity to 2,2'-methylenebis(4-methylphenol)] for the selective hydroxyalkylation of p-cresol. At equal level of Sn loading, Sn/Si-MCM-41 prepared by direct hydrothermal synthesis showed higher activity than Sn-impregnated Si-MCM-41 catalyst.